Differences in flavourant levels and synthetic coolant use between USA, EU and Canadian Juul products. Issue 4 (27th April 2020) - Erythropel, Hanno C; Anastas, Paul T; Krishnan-Sarin, Suchitra; O'Malley, Stephanie S; Jordt, Sven Eric; Zimmerman, Julie B
Abstract : Background: 'Juul' is the dominant US e-cigarette brand and was recently introduced to Canada, UK, France, Germany and Italy, with several flavours available across countries. US/Canadian products are sold with 5%, 3% and 1.5% (Canada only) nicotine content, whereas European Union (EU) regulation limits nicotine content to 1.7%. The differential nicotine content raises the question if flavour profiles and Juul device power output differ between countries. Methods: 'Mint', 'Vanilla' and 'Mango' e-liquids from all six countries were purchased in 2019 and analysed by GC/MS for their principal flavourant and nicotine content. In addition, device power specifications were compared for devices purchased from the respective countries. Results: Compositions of Juul e-liquids from the USA and Canada were identical and differed from the EU-marketed liquids, in which principal flavourant concentrations were significantly lower. EU Juul 'Mint' e-liquids contained a synthetic coolant, N-ethyl-p-menthane-3-carboxamide (WS-3), absent in US/Canadian products. US/Canadian 'Mango' e-liquid contained triethyl-citrate, an emulsifier. Nicotine contents matched label information, and devices had identical power specifications. Conclusions: Tested US/Canadian Juul e-liquids contained higher flavour concentrations than EU products, likely reflecting adaptation to user preferences. In EU, 'Mint' e-liquid, menthol is partially substituted with the synthetic coolant WS-3 that elicits a cooling effect like menthol but lacks its distinct 'minty' odour. The inhalational safety of WS-3 is unknown. The use of an emulsifier in US/Canadian 'Mango' Juul e-liquid may be necessary to keep the product homogeneous. Similar power specifications of devices between countries suggest that nicotine aerosol delivery is likely proportional to the e-liquid nicotine content.